Patient safety culture in the maternal-child area of a university hospital - Vitoria Sandri Pedroni; Helga Geremia Gouveia; Letícia Becker Vieira; Wiliam Wegner; Adriana Catarina de Souza Oliveira; Maxuel Cruz dos Santos; Franciela Delazeri Carlotto
ABSTRACT Objective: To describe the safety culture of the patient from the perspective of nurses and physicians working in the maternal-child area. Method: A cross-sectional study conducted from January to September 2018 with 41 professionals of the Obstetrics Center and obstetric hospitalization of a university hospital in the south of the country. The Hospital Survey on Patient Safety Culture was used, with 12 dimensions of the safety culture, measured by means of a general score (0 to 10) and of positive answer percentages to assess strengths and weaknesses. Results: The action of supervisors/bosses can be considered a strength of patient safety, with 78.2% of positive answers; already regarding communication, it was considered a fragility, punctuating 13.24%. The general safety grade of the patient assigned to the work's unit was very good, in a confidence interval of 95%. Conclusion: With the identification of the strengths and weaknesses of patient safety, it is possible to plan improvement actions. We emphasize that the non-punitive approach is essential.